Pendampingan Pengenalan Budaya Sekolah Pada Calon Guru Sekolah Dasar STKIP Pangeran Dharma Kusuma - Rochim, Ahmad Abdul; Khayati, Amal (STAI Publisistik Thawalib Jakarta, 2023)
The purpose of the assistance is to introduce school culture, student character and learning processes to prospective teachers before becoming educators. The implementation method is with lectures and mentoring by mentors (principals and teachers) which are carried out for 2 weeks during school effective hours. Media used: books, classrooms, teaching media, school environment. Implementation results: prospective educators, namely students, have a better understanding of school culture, get to know the character of students and increase their knowledge in the field of teaching because prospective educators (students) can practice good teaching methods in the classroom with the help of mentors.